Helminth Fauna of bats (Chiroptera) of the National Park «Smolny» (European Russia) - N. Yu. Kirillova; A. A. Kirillov (Российский паразитологический журнал)
The purpose of the research is to study the fauna of parasitic worms of bats (Chiroptera) in the National Park «Smolny» (Republic of Mordovia).Materials and methods. In 2018–2021, the helminth fauna of 445 ind. of 8 bat species at 10 locations in the National Park «Smolny» was studied using the method of complete helminthological necropsy. Parasitic worms were collected, fixed and processed using standard methods.Results and discussion. A total of 31 helminth species were recorded in bats of the National Park "Smolny": 3 – cestodes, 20 – trematodes and 8 – nematodes. The trematode Prosthodendrium cryptholecithum and the larva of the nematode Physaloptera clausa were found for the first time in Russian bats. The trematodes Gyrabascus amphoraeformis and G. oppositus were found for the first time in bats of the Middle Volga Region. The determining factors of helminth infection of bats are feeding predominantly on aquatic insects and poor contact of animals with the terrestrial environment. Of the 31 species of parasites found in bats, 28 species are specific parasites of bats, which is explained by the ecological isolation of this group of flying mammals and the antiquity of the co-evolution of bats and their parasites. An annotated list of helminths of bats is given, including their systematic position, host range, localization, infection rates, sites of detection and distribution. Among bats, the helminth fauna of the common noctule (15 species), Daubenton's bat (13) and Nathusius' pipistrelle (12) is the richest. The helminth fauna of the pond bat (6 species), lesser noctule (5) and Natterer's bat (4) is less represented. The greatest distribution in bats of the National Park "Smolny" has the trematode Plagiorchis koreanus and the nematode Pterothominx neopulchra noted each in 6 species of hosts. Only one helminth species (nematode Physocephalus sexalatus), which is of medical and veterinary importance as the causative agent of a dangerous helminthosis, has been recorded in bats.